Efek Fermentasi Anaerob terhadap Kadar Sianida Biomas Tanaman Singkong Pahit (Manihot Esculenta) - Yuli Retnani; T. Sutardi; M. Sitorus (Buletin Ilmu Makanan Ternak, 1990)
The research was done to rest: a) If anaerob fermentation could destroy cyanogenic glucoside, b) If silage of cassava plant, which was high in nutritive value and low cyanide content, was influenced by the proportion of roots, stems and leaves in the silage. The material used in this research was Pengkang variety, a bitter cassava plant, a nine months old. The treatments were 10 different silage of ration for silage with different periods of fermentations, i.e: 0, 7, 21 and 35 days. The split plot design and polynomial orthogonal test were applied for the statistical analysis.The result of this experiment showed that the decreasing in cyanide acid content was affected by the fermentation period (p<0.01), the proportion of cassava plant biomass (p<0.01) as well as by the interaction between the fermentation period and the proportion of cassava plant biomass (p<0.01). The best silage was obtained from the cassava plant biomass that consisted of 25% roots, 25% stems and 50% leaves that was fermented for 21 days. This silage had the lowest cyanide acid content, and the highest crude protein, crude fiber, TDN content and as well as the highest digestibility for Ruminants.